Mochammad Natsir dan Pemikiran Ekonomi Ummat 1950-1960 - Emalia, Imas (Buletin Al-Turas, 2013)
Abstract This article is intended as an attempt to reconstruct the history of thought from a figure of the famous politician who is soft, firm, and islamic behave, Mochammad Natsir. His thoughts about the economy of the Muslims is as his fight in Indonesia peopleâ€™s destinies take notice, especially Muslims. During his life in pursuit of economic Natsir Mochammad Muslims either when he politicking, of community, and preaching. Related to the economic development of this Ummah, Mochammad Natsir championed economic development via the Ummah Party Mayumi, the largest Islamic Ummah as the party at the time. In discussing character Mochammad Natsir, has always been in the political discussion, whether its action in politics or also his idea about politics that inevitably associated with Islam, very little discussion about his thinking in the field of Economics, but it turns out that economics is concerned Natsir Mochammad Ummah, generally the people of Indonesia. His thoughts on the economy is very inspiring and uplifting for the people of Indonesia to be able to maintain his life struggling to avoid poverty, squalor, misery, and suffering due to the behavior of those who blackmail her life wander the property. His idea about Islamic economic development Mochammad Natsir Ummah who looks at and strive to let the Muslims during the post-revolution until the 1960 's can live peaceful, prosperous, far from suffering, poverty, misery, and always pay attention to the messages from the teachings of Islam. Message from thinking this is about Mochammad Natsir human duty to care for and respect each other, because that is the nature of a human being as an independent creature who had to work hard in the face of the Earth to avoid poverty. This paper, entitled "the Economic Thinking and Natsir Mochammad Ummah 1950-1960".---AbstrakMakalah ini dimaksudkan sebagai usaha merekonstruksi sejarah pemikiran dari seorang sosok politikus terkenal yang lembut, tegas, dan islami, yakni Mochammad Natsir. Pemikirannya tentang ekonomi ummat adalah sebagai perjuangannya dalam memperhatikan nasib rakyat Indonesia, terutama ummat Islam. Selama hidupnya Mochammad Natsir memperjuangkan ekonomi ummat baik ketika ia berpolitik, bermasyarakat, dan berdakwah. Terkait dengan pembangunan ekonomi ummat ini, Mochammad Natsir memperjuangkan pembangunan ekonomi ummat melalui Partai Mayumi, sebagai partai ummat Islam terbesar saat itu. Dalam membahas tokoh Mochammad Natsir, selama ini selalu pada pembahasan politik, baik kiprahnya dalam berpolitik atau juga pemikiran-pemikirannya tentang politik yang pasti dikaitkan dengan Islam, sangat sedikit pembahasan tentang pemikirannya di bidang ekonomi, padahal ternyata Mochammad Natsir sangat memperhatikan ekonomi ummat Islam, umumnya rakyat Indonesia. Pemikirannya tentang ekonomi sangat memberikan inspirasi dan semangat bagi rakyat Indonesia untuk dapat berjuang mempertahankan hidupnya yang terhindar dari kemiskinan, kemelaratan, kesengsaraan, dan penderitaan akibat perilaku pemerasan dari mereka yang hidupnya bergelimang harta. Untuk itu makalah ini akan menyoroti Pemikiran Mochammad Natsir tentang pembangunan ekonomi ummat yang memandang dan mengusahakan agar umat Islam pada periode pasca revolusi sampai tahun 1960 dapat hidup damai, sejahtera, jauh dari penderitaan, kemiskinan, kesengsaraan, dan senantiasa memperhatikan pesan-pesan dari ajaran agama Islam. Pesan dari pemikiran Mochammad Natsir ini adalah tentang tugas manusia untuk menjaga dan menghormati sesamanya, karena ituÂ  adalah fitrah seorang manusia sebagai makhluk yang merdeka yang harus bekerja keras di muka bumi untuk menghindari kemiskinan. Makalah ini berjudul â€œMochammad Natsir dan Pemikiran Ekonomi Ummat 1950-1960â€.